Analisis Pengendalian Jumlah Cacat Produksi Kaos dengan Pendekatan Seven Tools (Studi Kasus: Markas Kaos Tulungagung) - Mahadi, Mohammad Afghan; Junianto, Dwi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Markas Kaos is a local garment industry engaged in screen-printed t-shirt production. In its operations, Markas Kaos faces the problem of a high number of defective products, which has an impact on decreasing production efficiency and product quality. This study aims to analyze the types of defects, their main causes, and the stability of the production process using the Seven Tools of Quality Control approach. The data used is secondary data on the number of production defects during the period January–December 2024. The results show that the dominant types of defects are long threads (34.70%), broken stitches (31.37%), wrinkles (22.10%), and holes (11.83%). The main factors causing defects come from human aspects, machines, materials, methods, and the work environment. Control chart analysis shows that the production process is in a statistically stable condition, because all defect proportion values are still within control limits. The results of this study are expected to serve as evaluation material for Markas Kaos management in improving product quality and production process efficiency on an ongoing basis.